Prevalence And Profits Of Insurers In The Administrative Services Only Market Serving Self-Insured Employers, 2010-22 - Abraham, Jean M; Cook, Amanda C; Sirmans, E Tice (Health affairs (Millwood, Va.), 2024)
For 165 million nonelderly Americans, employers provide health insurance either by purchasing a fully insured plan or through self-insurance. By self-insuring, employers bear the financial risk for enrollees' health care spending and are accountable for plan management, either directly or by contracting with a third-party administrator. Using National Association of Insurance Commissioners data, we demonstrate that insurers are deeply entrenched in the provision of administrative services only (ASO) contracts for self-insured employers. In 2022, insurers administered to nearly four times as many ASO enrollees as they covered in fully insured plans, with fifty-six insurer-based ASO contractors providing services for 118 million enrollees. The largest ASO contractors-CVS Group, Cigna Health Group, and Elevance Health Inc. Group-collectively served more than seventy million ASO enrollees and demonstrated less variable and stronger profitability relative to other ASO contractors. This study expands understanding of this increasingly important market for employer-sponsored insurance.